Improving the flame retardancy and mechanical properties of poly(lactic acid) with a novel nanorod-shaped hybrid flame retardant. Issue 18 (4th February 2016) - Cao, Yu; Ju, Yaqing; Liao, Fenghui; Jin, Xiaoxun; Dai, Xiu; Li, Jiawei; Wang, Xinlong
Abstract : A novel nanorod-shaped hybrid flame retardant (NRH-FR) was synthesized by the reaction of benzenephosphinic acid with powdery aluminium hydroxide and the PLA/NRH-FR nanocomposites with good flame retardancy and mechanical property were prepared. Abstract : A novel nanorod-shaped hybrid flame retardant was synthesized by the reaction of benzenephosphinic acid (BPA) with powdery aluminium hydroxide and was analyzed by SEM, XRD, XPS and contact angle tests. Nanocomposites of poly(lactic acid) (PLA) with the flame retardant were prepared. The prepared nanocomposites had good mechanical properties and the tensile strength of the nanocomposite containing 10 wt% nanorods reached 82.51 MPa. Besides, the storage modulus increased about 39.2% for the composites with 10 wt% loading of the flame retardant compared with neat PLA at 25 °C. Meanwhile, the LOI of the nanocomposite was about 25.0% and a V-0 rating in UL-94 was attained in the case of 30 wt% of the flame retardant compared to 20.0% and no rating for pure PLA. SEM observations of the fractured surfaces showed that the nanocomposites had good interfacial interaction, which resulted in the improvement of mechanical properties. The addition of the hybrid flame retardant led to the formation of a coherent and tight char layer as well as the production of PO2 ˙ radicals and water, which retarded the combustion process of PLA.